Defective autophagy is a key feature of cerebral cavernous malformations. Issue 11 (28th September 2015) - Marchi, Saverio; Corricelli, Mariangela; Trapani, Eliana; Bravi, Luca; Pittaro, Alessandra; Delle Monache, Simona; Ferroni, Letizia; Patergnani, Simone; Missiroli, Sonia; Goitre, Luca; Trabalzini, Lorenza; Rimessi, Alessandro; et al.
Abstract: Cerebral cavernous malformation (CCM) is a major cerebrovascular disease affecting approximately 0.3–0.5% of the population and is characterized by enlarged and leaky capillaries that predispose to seizures, focal neurological deficits, and fatal intracerebral hemorrhages. Cerebral cavernous malformation is a genetic disease that may arise sporadically or be inherited as an autosomal dominant condition with incomplete penetrance and variable expressivity. Causative loss‐of‐function mutations have been identified in three genes, KRIT1 ( CCM1 ), CCM2 (MGC4607), and PDCD10 ( CCM3 ), which occur in both sporadic and familial forms. Autophagy is a bulk degradation process that maintains intracellular homeostasis and that plays essential quality control functions within the cell. Indeed, several studies have identified the association between dysregulated autophagy and different human diseases. Here, we show that the ablation of the KRIT1 gene strongly suppresses autophagy, leading to the aberrant accumulation of the autophagy adaptor p62/SQSTM1, defective quality control systems, and increased intracellular stress. KRIT1 loss‐of‐function activates the mTOR‐ULK1 pathway, which is a master regulator of autophagy, and treatment with mTOR inhibitors rescues some of the mole‐cular and cellular phenotypes associated with CCM. Insufficient autophagy is also evident in CCM2 ‐silenced human endothelial cells and in both cells and tissues from an endothelial‐specific CCM3 ‐knockout mouse model, as well as in human CCM lesions. Furthermore, defective autophagy is highly correlated to endothelial‐to‐mesenchymal transition, a crucial event that contributes to CCM progression. Taken together, our data point to a key role for defective autophagy in CCM disease pathogenesis, thus providing a novel framework for the development of new pharmacological strategies to prevent or reverse adverse clinical outcomes of CCM lesions. Synopsis: This study provides new evidence on the mechanisms underlying cerebral cavernous malformation (CCM) disease pathogenesis, opening the prospect and offering valuable clues for the development of novel therapeutic approaches based on the regulation of the autophagic process. KRIT1 deletion in murine and human endothelial cell lines results in autophagy defects that cause aberrant accumulation of the autophagy adaptor p62/SQSTM1 and aggresome‐like structures. Impaired autophagy in KRIT1 deficient endothelial cells is accompanied by over‐activation of mTOR signaling pathway, suggesting novel targets for therapeutic intervention. Defective autophagy underlies major phenotypic signatures of CCM disease, including EndMt that contributes to CCM disease progression. mTOR inhibitors restore autophagy in KRIT1‐depleted cells and rescue molecular and cellular disease phenotypes, thus alleviating potential causes of CCM lesion formation and progression. Defective autophagy and consequent p62/SQSTM1 accumulation are common features of loss‐of‐function mutations of the three known CCM genes. Abstract : This study provides new evidence on the mechanisms underlying cerebral cavernous malformation (CCM) disease pathogenesis, opening the prospect and offering valuable clues for the development of novel therapeutic approaches based on the regulation of the autophagic process.